Postoperative delirium is a risk factor for complications and poor outcome after total hip and knee arthroplasty - Meyer, Matthias; Götz, Julia; Parik, Lukas; Renkawitz, Tobias; Grifka, Joachim; Maderbacher, Günther; Kappenschneider, Tobias; Weber, Markus (Acta orthopaedica, 2021)
Background and purpose — Improving health care and demographic change have resulted in a steady increase in geriatric patients undergoing total hip (THA) and knee (TKA) arthroplasty. Postoperative delirium (POD) is a frequent and severe complication after major surgery. Therefore, we analyzed the impact of POD on outcome after THA and TKA.Patients and methods — In a consecutive series of 10,140 patients who had undergone elective THA or TKA between 2011 and 2020, rates of reoperation within 90 days, readmission within 90 days, complications, and responder rate as defined by the OMERACT-OARSI criteria were compared between patients with and without POD. Multivariable logistic regression models were used to assess the relationship between POD and other postoperative complications.Results — Patients with POD showed higher rates of reoperation (12% vs. 5%), readmission (15% vs. 5%), surgical complications (7% vs. 2%), non-surgical complications (8% vs. 4%), Clavien-Dindo IV° complications (10% vs. 2%) and transfusion (14% vs. 2%). POD led to lower responder rate (76% vs. 87%) 1 year after total joint replacement. All previous comparisons statistically significant. Multivariable logistic regression analyses revealed POD as an independent risk factor for reoperation (OR = 2; CI 1-3), readmission (OR = 2; CI 2-4) and Clavien-Dindo IV° complications (OR = 3; CI 2-5).Interpretation — POD is a serious problem in elective joint replacement. Affected patients suffer more complications and show poor patient-reported outcome 1 year postoperatively. Systematic prevention strategies and standardized therapy protocols are mandatory to avoid burden to patients and healthcare providers.
Gesehen am 16.12.2021